Investigating factors underlying why householders remain in at-risk areas during bushfire disaster in Australia - Olufisayo Adedokun; Temitope Egbelakin; Willy Sher; Thayaparan Gajendran (Heliyon, 2024)
Although most homes lack design and construction features to withstand bushfires, there is a growing trend of householders relocating to bushfire-prone areas. Notably, many bushfire-related fatalities have occurred within proximity, specifically within 100 m of bushland. Therefore, this paper explores the factors that drive householders to remain in at-risk areas, despite the imminent threat of bushfires. Thirty semi-structured interviews were conducted with participants residing in the southeastern region of New South Wales (NSW). The interviews were recorded, transcribed using Otter.AI, and subjected to thematic analysis using NVivo 12 Pro. The findings shed light on why certain householders decided to stay on their properties during the catastrophic 2019/2020 bushfires. Upon analysis, we uncovered thirty-six distinct factors that underlie householders’ choices to remain during bushfires. These factors were categorized into nine groups: protection-related, attitude-related, information-related, operation-related, road-related, shelter-related, finance-related, health-related, and rebuilding-related factors. The study underscores the importance of understanding gender-based differences and pet ownership in bushfire evacuation decisions, emphasizing the need for tailored communication strategies. These findings hold several important implications for research and practice regarding early self-evacuation from bushfires.